The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1111/epi.17033
|View full text |Cite
|
Sign up to set email alerts
|

SUDEP‐3: probable improvement in risk stratification for sudden death in epilepsy

Abstract: To the Editors, We thank Dr. Tarighati Rasekhi et al. for raising an important issue in sudden unexpected death in epilepsy (SUDEP) research: the risk stratification for sudden death in epileptic patients. We have carefully reviewed their recent article in Epilepsia titled, Improving prediction of sudden unexpected death in epilepsy: From SUDEP-7 to SUDEP-3, 1 and we wish to share our experience regarding SUDEP-3 and SUDEP-7 scales for sudden death risk stratification in patients with epilepsy.In our center at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In addition, the only other published study of the SUDEP-7 found that it had poor correlation with SUDEP (Odom and Bateman). 4 We appreciate the feedback to date regarding the SUDEP-3 inventory, including a recent report highlighting the utility of the SUDEP-3 inventory 5 and are enthusiastic about further evaluations of the new inventory in larger cohorts.…”
Section: Response: Sudep-7 Inventory: Validation In a Retrospective Cohort Studymentioning
confidence: 99%
“…In addition, the only other published study of the SUDEP-7 found that it had poor correlation with SUDEP (Odom and Bateman). 4 We appreciate the feedback to date regarding the SUDEP-3 inventory, including a recent report highlighting the utility of the SUDEP-3 inventory 5 and are enthusiastic about further evaluations of the new inventory in larger cohorts.…”
Section: Response: Sudep-7 Inventory: Validation In a Retrospective Cohort Studymentioning
confidence: 99%